2012
DOI: 10.1590/s1983-40632012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Emergência de plântulas de pequizeiro em função da planta matriz e uso de ácido giberélico

Abstract: Em Goiás, o pequi (Caryocar brasiliense) se destaca, dentre as frutíferas nativas do Cerrado, como promissora para a produção comercial. Um dos obstáculos para a sua produção em grande escala, no entanto, é o fato de que a germinação de sementes seja baixa e irregular. Com o objetivo de avaliar a emergência de sementes de pequizeiro e o desenvolvimento inicial de mudas oriundas de 16 plantas, aos dez meses após a colheita, na presença e ausência de ácido giberélico (GA3), foram conduzidos dois experimentos. O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
2
2
0
4
Order By: Relevance
“…Seed size also affected the final seedling emergence percentage, once the accumulated emergence in small seeds was about 20% after one year (Figure 1), whereas in medium and large ones (> 40 mm length) the accumulated emergence exceeded 30%. These emergency rates agree with the results obtained by Leão et al (2012), who observed germination rates varying from 3% to 56% in pequizeiro seeds.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Seed size also affected the final seedling emergence percentage, once the accumulated emergence in small seeds was about 20% after one year (Figure 1), whereas in medium and large ones (> 40 mm length) the accumulated emergence exceeded 30%. These emergency rates agree with the results obtained by Leão et al (2012), who observed germination rates varying from 3% to 56% in pequizeiro seeds.…”
Section: Resultssupporting
confidence: 92%
“…In these seeds, emergence extended until about 1 year after sowing (Figure 1). Similar results were obtained by Leão et al (2012), who observed the emergence of pequizeiro seedlings up to 128 days after seed sowing.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Ao estudar o efeito do uso do GA 3 na emergência de plântulas de piquizeiro (Caryocar brasiliense Camb. ), LEÃO et al (2012) averiguaram que dentre as sementes das 16 plantas matrizes avaliadas, somente as sementes da matriz 6 apresentaram o menor TME de plântulas, independente do tratamento utilizado (imersão em água ou em 500 mg L -1 de GA 3 por 48 h). A avaliação da APA (Tabela 4) evidenciou que não ocorreu interação entre as concentrações do GA 3 e os períodos de fermentação, e que isoladamente os referidos fatores também não proporcionaram diferença significativa na APA das plântulas de romã, cujo comprimento médio ficou em torno de 3,1 cm plântula FIGURA 2.…”
Section: Tabela 2 Porcentagem De Emergência (Pe) íNdice De Velocidaunclassified